Postpartum depression in Gujarat, India: Associations with social support, breastfeeding attitudes, and self-efficacy - Bhumika Surati; M Yogesh; Raza Munshi; Roshni Vamja (Journal of Family Medicine and Primary Care)
Background: Postpartum depression (PPD) is a significant public health concern with detrimental effects on maternal and child well-being. Social support, breastfeeding attitudes, and self-efficacy have been identified as potential protective or risk factors for PPD. This study aimed to investigate the associations between PPD, social support, breastfeeding attitudes, and self-efficacy among postpartum women in Gujarat, India. Methods: A cross-sectional study was conducted among 403 postpartum women in Gujarat, India. Data on sociodemographic characteristics, obstetric factors, PPD (assessed using the Edinburgh Postnatal Depression Scale), social support, breastfeeding attitudes, and self-efficacy were collected through structured interviews. Bivariate and multivariate logistic regression analyses were performed to examine the associations between PPD and the independent variables. Results: The prevalence of PPD in the study population was 50.1% (n = 202), with 28.8% (n = 116) experiencing mild depression, 16.6% (n = 67) moderate depression, and 4.7% (n = 19) severe depression. Lower educational level (n = 120, 29.8%; AOR: 1.72, 95% CI: 1.04–2.85), lower socioeconomic status (n = 242, 60%; AOR: 1.84, 95% CI: 1.12–3.02), non-exclusive breastfeeding (n = 167, 41.4%; AOR: 1.68, 95% CI: 1.11–2.54), low social support (n = 101, 25.1%; AOR: 2.51, 95% CI: 1.57–4.02), and a history of depression (n = 93, 23.1%; AOR: 2.94, 95% CI: 1.82–4.75) were significantly associated with higher odds of PPD in the multivariate analysis. In addition, negative breastfeeding attitudes and low self-efficacy levels were associated with increased odds of PPD. Conclusions: The findings highlight the significant associations between PPD and various sociodemographic, obstetric, and psychosocial factors among postpartum women in Gujarat, India. Interventions targeting social support, breastfeeding attitudes, and self-efficacy, as well as targeted support for women with identified risk factors, may help mitigate the burden of PPD and promote maternal well-being.